2008
DOI: 10.1111/j.1743-6109.2008.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

C-Type Natriuretic Peptide Hyperpolarizes and Relaxes Human Penile Resistance Arteries

Abstract: Introduction In addition to nitric oxide (NO), it is thought that an endothelium-derived hyperpolarizing factor (EDHF) plays an important role in the relaxation of penile arteries. Recently, it has been shown that C-type natriuretic peptide (CNP) shows the characteristics of EDHF in systemic small arteries. Aim To investigate the mechanism involved in CNP-evoked vasodilatation and to address whether CNP is an EDHF in human pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 53 publications
2
44
0
1
Order By: Relevance
“…Under physiological conditions, the endothelium exerts regulatory effects on vasodilatation, as it releases numerous vasoactive substances, such as NO, bradykinin, prostaglandin I2, substance P and so on. EDHF is another vasoactive substance and it has been found in rat, horse and human penile small arteries [5][6][7][8]17]. Moreover, in systemic arteries, several EDHF candidates have been suggested, including potassium ions, products of the cytochrome P450 pathway, C-type natriuretic peptide, hydrogen peroxide and K + [7,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under physiological conditions, the endothelium exerts regulatory effects on vasodilatation, as it releases numerous vasoactive substances, such as NO, bradykinin, prostaglandin I2, substance P and so on. EDHF is another vasoactive substance and it has been found in rat, horse and human penile small arteries [5][6][7][8]17]. Moreover, in systemic arteries, several EDHF candidates have been suggested, including potassium ions, products of the cytochrome P450 pathway, C-type natriuretic peptide, hydrogen peroxide and K + [7,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…EDHF is another vasoactive substance and it has been found in rat, horse and human penile small arteries [5][6][7][8]17]. Moreover, in systemic arteries, several EDHF candidates have been suggested, including potassium ions, products of the cytochrome P450 pathway, C-type natriuretic peptide, hydrogen peroxide and K + [7,18,19]. EDHF-mediated relaxation is dependent on the activation of endothelial SK3 and IK1, which can be blocked by the combination of apamin and charybdotoxin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAM responses to CNP were blocked by glibenclamide, revealing for the first time a critical involvement of K ATP in CNP's endothelial effects. These actions of CNP are likely mediated via activation of the NPR-C receptor (also referred as natriuretic peptide clearance receptor), whose signaling is required for CNP-dependent hyperpolarization, vasorelaxation, and endothelial growth (Villar et al, 2007;Kun et al, 2008;Khambata et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…2,[16][17][18][19] Early studies in dogs showed that intracavernous injection of adenosine induced a full erection, which was independent of acetylcholine. 20 Takahashi et al 21 further investigated the hemodynamic effects of intracavernous injection of adenosine in dogs.…”
Section: Adenosine Signaling and Penile Erection Exogenous Adenosine mentioning
confidence: 99%